Kritična analiza politizacije državne uprave v Sloveniji - Čehovin, Marko (Teorija in praksa, 2014)
Even though some level of politicisation is pressed into the "genetic material" of administrative system, the majority of experts agree that a system with high levels of politicisation is less efficient because a large share of individuals do not have the chance to develop to their full potential. The negativity of politicisation is even more devastating in smaller states like Slovenia since those states have a limited set of human resources available. On the basis of a detailed analysis of the state administration' politicisation in Slovenia, the authors can confirm that the level of politicisation is quite high; after the country's accession to the European Union (2004) and adoption of so-called saving laws (2010-2013) this politicisation trend is even strengthening. Despite the formal existence of mechanisms of a meritocratic state administration system, politicians play an increasingly decisive role in the employment and advancement of civil servants, and are in total control of the appointment and dismissal of high-ranking civil servants. The predominance of politicians in their relationship towards civil servants can be changed via relatively simple changes to formal normative acts and so the authors also propose seven priority proposals to bring about less politicisation.
Keywords: državna uprava; državni uradniki; javna uprava; politični funkcionarji; politizacija; Slovenia; Slovenija